Real-life dental examination elicits physiological responses different to visual and auditory dental-related stimuli. - Tadea Košir (Public Library of Science (PLoS), 2021)
Background Previous studies on dental anxiety have examined the psychophysiological responses evoked in dentally anxious subjects by dental-related stimuli, but not during a real-life dental examination, which was achieved in the present study. Methods The heart rate, skin conductance level, and heart rate variability of 25 subjects with dental anxiety and 25 healthy controls were examined. Anxiety was determined by the Modified Dental Anxiety Scale and the Dental Anxiety Scale-Revised. The psychophysiological reactions of the two groups were compared during exposure to dental-related pictures, dental-related sounds, and an actual examination in a dental surgery. Results All the dental-related stimuli provoked an increase in heart rate, i.e. visual stimuli (p<0.001; 95% CI 0.98-3.95 bpm), auditory stimuli (p<0.001; 95% CI 1.34-4.99 bpm), and a dental examination (p<0.001; 95% CI 1.26-5.39 bpm). Dental-related pictures provoked inferior skin conductance level changes compared to dental-related sounds and the dental examination (visual modality vs auditory p<0.001; 95% CI 0.039-0.152; visual modality vs examination p<0.001; 95% CI 0.083-0.275). Heart rate variability manifested in a complex pattern of responses to the dental examination. However, when exposed to all three dental-related stimuli presentation conditions, the heart rate (F = 0.352, p = 0.556), skin conductance level (F = 0.009, p = 0.926), and heart rate variability parameters of subjects with dental anxiety did not differ in comparison to the healthy controls. Conclusions This pilot study represents an evaluation of psychophysiological reactions during a real-life dental examination compared to single modality stimuli, and shows that a real-life dental examination provokes an increase in heart rate, heart rate variability and skin conductance level. Additionally, autonomic responses did not differ between the experimental and control groups. The key issue for future studies is the effect of real-life situations on the physiological and psychological state of the subjects, which should be considered when planning new research and studied in depth.